Administrative Review of the Treaty of Waitangi Settlement Process - Andrew, Jessica (Victoria University of Wellington Law Review, 2008)
This paper looks at administrative review of the negotiation and settlement process for Treaty of Waitangi historical claims. The foundation is an analysis of the current treatment of these claims within the political arena, the Waitangi Tribunal and the courts. This includes a detailed analysis of the effectiveness of political and Waitangi Tribunal responses, and a hard look at the validity of the courts' continued stance that Treaty settlement cases are non-justiciable. Due to the non-binding nature of its recommendations, the effectiveness of the Waitangi Tribunal depends largely on the existence of political buy-in from the Executive and political branches of government. Analysis of the evidence illustrates that this buy-in is lacking. Despite the intensity of Waitangi Tribunal scrutiny in this area, very few meaningful outcomes are being achieved. Finally, the discussion of the courts' response to Treaty settlement claims looks closely at the concept of non-justiciability and the courts' continued application of broad precedents without meaningful analysis. This paper argues that a thorough understanding of the cases brought before the courts illuminates differences between those precedents being applied and the cases now being heard. Declaring a case non-justiciable has serious consequences and should not be done lightly.